Media Use and Knowledge of Cervical Cancer among Women in Delta State Nigeria (2015)
The mass media are employed in carrying out campaigns about important health issues such as HIV/AIDS, family planning, drug abuse and diabetes. Although studies have focused on the influence of such campaigns on the general behaviour of the public, there are no documented studies that examined media use and knowledge of cervical cancer among women in Delta State, South-South Nigeria. This study, therefore, investigated media use among women in Delta State, Nigeria in relation to their knowledge of cervical cancer. Survey and in-depth interview (IDI) research designs were employed in carrying out the study. Atotal of 340 respondents and 15interviewees comprising women between the ages of 15 and 50years were purposively selected for the study. The finding revealed no relationship between women's media use and knowledge of cervical cancer. There is urgent need to educate women on cervical cancer as failure to recognize early symptoms contributes to poor prognosis common in Nigerian women. Considering that the mass media have the potential that can be harnessed to provide people with adequate knowledge needed to contain the scourge, organizations/agencies that are involved in health campaigns should consider aggressive use of mass media(radio, television, newspaper and magazine) cervical cancer campaign in order to tackle this menace.